2018
DOI: 10.1177/2309499017754104
|View full text |Cite
|
Sign up to set email alerts
|

The role of teriparatide in tuberosity healing after reverse shoulder arthroplasty in complex proximal humeral fragility fracture

Abstract: Introduction: Tuberosity healing is known to be one of the factors that increase functional outcome in Reverse Total Shoulder Arthroplasty (rTSA). In fragility fractures, tuberosity healing is difficult to be achieved. The fragment stability and bone-forming agent application become strategies to overcome this problem. The purpose of this study was to evaluate the benefit of teriparatide application to promote tuberosity union in rTSA on four-part proximal humeral fractures to achieve better functional outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Anatomical tuberosity healing and rotator cuff integrity have been shown to be essential for good functional recovery after HA for PHFs [ 41 – 43 ]. The unreliable results achieved with HA in the elderly suffering from cPHFs led to attempts to treat these patients with RSA, since the functional outcomes are less dependent on tuberosity healing and cuff integrity [ 13 15 , 19 , 20 , 44 , 45 ]. However, recent studies have demonstrated that although tuberosity healing is not a prerequisite for a satisfactory outcome after RSA for cPHFs, it still leads to better clinical results [ 21 27 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical tuberosity healing and rotator cuff integrity have been shown to be essential for good functional recovery after HA for PHFs [ 41 – 43 ]. The unreliable results achieved with HA in the elderly suffering from cPHFs led to attempts to treat these patients with RSA, since the functional outcomes are less dependent on tuberosity healing and cuff integrity [ 13 15 , 19 , 20 , 44 , 45 ]. However, recent studies have demonstrated that although tuberosity healing is not a prerequisite for a satisfactory outcome after RSA for cPHFs, it still leads to better clinical results [ 21 27 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, monitoring changes in bone density before surgery in patients with rotator cuff tears requiring RSA is crucial. Postoperative administration of teriparatide and denosumab is reportedly effective in maintaining bone quality around artificial joints [29][30][31][32]. Hence, we strongly recommend that osteoporosis drugs should be considered after surgery.…”
Section: Discussionmentioning
confidence: 99%